Maintenance management of Sekolah Agama Rakyat in Kelantan / Mohd Khairul Mat Jusof - Mat Jusof, Mohd Khairul (Faculty of Architecture, Planning and Surveying, 2008)
This dissertation is about a maintenance management of Sekolah Agama Rakyat (SAR) in Kelantan. This study lay down to identify and know a maintenances management and maintenances strategy at SAR. It also identify problems that appears in school environment, indoor and outdoor. To look and identify a level or condition, facilities, amenities that available in that institution. A information about all purposed of maintenances management at SAR are collected through a research at SAR, which each school are separate either it is Under government or Under Non-Government. As a case study, school that selected are SMA Maahad Muhammadi Kota Bharu, SMA Maahad Muhammadi Pasir Mas, SMA Diniah To’Uban, SMA Pohon Buluh, SMA Rahmaniah and SMA Peringat. At every case study, questionnaires were distributed to teachers, school staff and students to know user perception, satisfaction of maintenances and building condition level. Interviews also were asked to school administration to know about their management and maintenance and an allocation that received for their institution. An observation at whole school area also conducted to look out a condition at each school building. After all information was collected, an analysis of interview, questionnaire and observation were finding. From analysis finding, we can look differences in aspect of management, allocation, building condition between SAR under government and under non-government. The further recommended to improving in the operation and maintenance system are recognized and solution will be specified in the end of chapter.